2017
DOI: 10.1177/1078390317704044
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Nurse Practitioner–Led Community-Based Service Model for Delivering Coordinated Care to Persons With Serious Mental Illness at Risk for Homelessness

Abstract: Mental health provisions in the recently passed 21st Century Cures Act support community mental health specialty treatment. The SPC provides a template for similar nurse practitioner-led models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…PMH APRNs deliver a good deal of education in their practice, and it would be informative to understand the types of education provided, that is, if it was regarding medication, symptom management, and/or recovey. In the New York City clinic previously described, the educational component of the PMH NP role was signifant (Baker et al, 2018). Detailed reporting on these aspects of PMH NP practice should be a component of all reports on PMH APRN service models and would help fill the gap on knowldege of APRN role activitites and their impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMH APRNs deliver a good deal of education in their practice, and it would be informative to understand the types of education provided, that is, if it was regarding medication, symptom management, and/or recovey. In the New York City clinic previously described, the educational component of the PMH NP role was signifant (Baker et al, 2018). Detailed reporting on these aspects of PMH NP practice should be a component of all reports on PMH APRN service models and would help fill the gap on knowldege of APRN role activitites and their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, additional sources that describe PMH APRN activities are the reports of practice models, often developed in an academic–practice partnership arrangement. In New York City a team of PMH NPs and their academic partner established a center for individuals who were homeless and dealing with serious mental illness (SMI; Baker, Travers, Buschman, & Merrill, 2018). The center was staffed exclusively by PMH NPs who provided both comprehensive mental health services and interventions to address social needs, such as housing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, many homeless clinics rely on volunteer medical providers as staff. The volunteer staff is not often able to provide stable long‐term provider–patient relationships, a prerequisite to a therapeutic medical relationship 22,27,37 . It has been demonstrated that dedicated family medicine physicians are well suited to manage the needs of homeless patients, providing continuity of care for patients and leadership for multidisciplinary teams 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The focus on population health will result in new models of care, such as the PMH APRN model developed in New York to address the needs of homeless individuals with serious mental illness (Baker, Travers, Buschman, & Merrill, 2018). It is unfortunate that this model could not be sustained due to billing and funding issues.…”
Section: Broader Influences On Workforce Developmentmentioning
confidence: 99%